Interbank funding as insurance mechanism for (persistent) liquidity shocks - Marcel Bluhm (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The interbank market is important for the efficient functioning of the financial system, transmission of monetary policy and therefore ultimately the real economy. In particular, it facilitates banks' liquidity management. This paper aims at extending the literature which views interbank markets as mutual liquidity insurance mechanism by taking into account persistence of liquidity shocks. Following a theory of long-term interbank funding a financial system which is modeled as a micro-founded agent based complex network interacting with a real economic sector is developed. The model features interbank funding as an over-the-counter phenomenon and realistically replicates financial system phenomena of network formation, monetary policy transmission and endogenous money creation. The framework is used to carry out an optimal policy analysis in which the policymaker maximizes real activity via choosing the optimal interest rate in a trade-off between loan supply and financial fragility. It is shown that the interbank market renders the financial system more efficient relative to a setting without mutual insurance against persistent liquidity shocks and therefore plays a crucial role for welfare.
urn:nbn:de:hebis:30:3-386562
Keywords: E44; E51; G01; G21; G28; 330; financial fragility; interbank market; liquidity; maturity; network model